Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Sanipak Indonesia - Febriyanda Prasetya; Triana Ananda Rustam (Universitas Batanghari Jambi, 2022)
The study was conducted to understand the impact of work environment and discipline on the performance of PT Sanipak Indonesia employees through the use of random sampling method. The framework used for this study is the independent variable, in the form of work environment and discipline, and thenÂ the dependent variable in the form of employee performance. The methods used are quantitative research methods and data dissemination techniques using questionnaires. ToÂ sample using Slovin's formula and get a total of 171 respondents, then all data were examined through the use of SPSS version 25. The results in this study stated that the R square score of around 0.665 and 66.5% proves that there is an environmental impact along with work discipline on employee performance. The t-test on the work environment variable obtained a significant score of 0.000 <0.05 andÂ count t that was 8.214 > 1.974 t tabletated that the work environment had a good and significant impact on employee performance, while the work discipline variable got a significant score of 0.000 <0.05 count t which is 4.363 > table t 1.974 which states that work discipline has a good and significant impact on employee performance and the results of the F test have a score of F count 166,689 > 3.05 F table and a significant value of about 0.000b < 0.05 states that the work environment and work discipline are simultaneously has a good and drastic impact on employee performance.